Hubungan Riwayat Hipertensi, Obesitas dan Usia Ibu dengan kejadian Preeklamsi di Rumah Sakit Muhammadiyah Palembang tahun 2022 - Ismarini, I.; Ciselia, Dewi; Afrika, Eka (NHM PRESS, 2023)
Hypertension in pregnancy or preeclampsia, needs special treatment because it can reduce blood flow to the placenta, which will affect the supply of oxygen and nutrients to the baby. This will slow down the growth of the baby and increase the risks during delivery. It is estimated that preeclampsia complicates 2-8% of pregnancies globally. In Latin America and the Caribbean, hypertensive disorders are responsible for almost 26% of maternal deaths, while in Africa and Asia, they contribute to 9%. In 2021 there were 7,389 deaths in Indonesia, one of the contributing factors was hypertension in pregnancy. The aim of this study was to determine the relationship between a history of hypertension, obesity, and age simultaneously with the incidence of preeclampsia in pregnant women at Muhammadiyah Palembang Hospital in 2022. The research design used is quantitative analytical research with a cross-sectional approach. The population in this study were all pregnant women who checked their pregnancies at the Palembang Muhammadiyah Hospital in 2022. A total of 1,708 people. The number of samples used in this study was 94. The results of univariate analysis of 94 respondents found 12 respondents (12.8%) experienced preeclampsia and those who did not experience preeclampsia were 82 respondents (98.2%). The results of the chi-square statistical test for the variable history of hypertension obtained ρ value = 0.000, the obesity variable ρ value = 0.001, the mother's age variable ρ value = 0.001 less than α = 0.05 indicating that there is a significant relationship between the history of hypertension and the incidence of preeclampsia at home Palembang Muhammadiyah Hospital in 2022. Suggestions for the leadership of the Muhammadiyah Hospital are that the results of this research can be used as input and information material for the hospital in making health programs for pregnant women, especially the problem of preeclampsia.